Ethics and Critical Care Medicine
XX, 236 p.
Keywords: The expense of critical care and emergency medicine, along with widespread expectations for good care when the need arises, pose hard moral and political problems. How should we spend our tax d'ollars, and who should get help? The purpose of this volume is to reflect upon our choices. The authors whose papers appear herein identify major difficulties and offer various solutions to them. Four topics are discussed throughout the volume: First, encounters between patients and health professionals in critical situations in general, and where scarcity makes rationing necessary; second, allocation and social policy, including how much to spend on preventive, chronic or critical care medicine, or for medicine in general compared to other important social projects; third, conflicts between or ranking of important goals and values; and fourth, conceptual issues affecting the choices we make. Since these topics are raised by the authors in almost every essay, we did not divide the papers into separate sections within the volume. Warren Reich begins the volume with a parable illustrating a key problem for contemporary medicine and two very different approaches to its solution. His story begins with the "delivery" of three indigent, critically ill, foreign patients to the emergency room of a large American private hospital. Although the hospital is legally bound to care for these patients, providing long term, high cost care for them and others soon becomes a major financial strain.